The 10 rules of successful nations - Ruchir Sharma, read by William Hughes ([London] Blackstone Publishing, 2020)
A wake-up call to economists who failed to foresee every recent crisis, including the cataclysm of 2008, The 10 Rules of Successful Nations is a slim primer full of pioneering insights on the political, economic, and social habits of successful nations.
Keywords: Economic development; Comparative economics